DIGITALIZATION MODEL OF CIAYUMAJAKUNING MANUSCRIPTS - Sutisna, Nanang; Putro, Sasongko S; Yusar, Dedi (International Review of Humanities Studies, 2023)
Intellectual activity in the archipelago was generally born in various kingdoms that existed at that time, one of which was in the Cirebon Kingdom. One of his works is in the form of a written tradition carried out by poets who gave birth to his writings under the direction of these kings. These writings are generally still in the form of handwriting which is often called manuscripts. In their writings they express their ideas or ideas in the form of values in general life such as religion, art, culture, history, medicine, government, technology, literature, culture, architecture and other life. Considering that the object of this research is ancient texts, especially in the Ciayumajakuning area which includes the Cirebon, Indramayu, Majalengka and Kuningan areas which were trading areas and the spread of Ismanism by the Cirebon Sultanate. The purpose of this study is to provide data in the form of digital photos and manuscript descriptions for the benefit of research studies and to bridge the gaps in knowledge in the context of social sciences, humanities and education. In addition, data collection from this manuscript will make an important contribution in mapping manuscripts in West Java. The urgency of research on the Cayumajakuning manuscript refers to aspects of the existence of ancient manuscripts and their relation to the surrounding community. Through this research, a correlation can be found between the people of Cayumajakuning who are familiar with the written tradition and those who are not familiar with this tradition.